BMP and noncanonical WNT signaling co-regulate the tail development in zebrafish - Yang, Yi (Kansas State University, 2010)
Multiple signaling pathways regulate development of the posterior zebrafish body, which is derived from a population of progenitor cells called the tailbud, a structure formed at the end of gastrulation. Fate specification and differentiation are closely linked with cell migration to ensure that, as some cells exit the tailbud and differentiate, other cells are retained in the tailbud as undifferentiated precursors to support later growth. The role of BMP signaling in specifying cell fate in the tailbud has been well-characterized. Among the lost ventral tissues like ventral tailfin and cloaca, embryos with compromised BMP signaling produce a curious phenotype-a ventrally located secondary tail containing both somitic muscle and notochord. This phenotype is proposed to be a fate-patterning defect when the BMP gradient lowered to a precise level. However, this morphogen mode is insufficient to explain secondary tail formation without considering BMP also regulates morphogenetic movements during gastrulation, promoting the convergence of lateral mesodermal cells towards the dorsal axis. In this study, we provide evidence that BMP signaling continues to mediate cell movements during tail development. Our data indicate that BMP signaling is activated in the ventroposterior tailbud to promote cell migration during tailbud protrusion, and that it is the defective migration of these cells which ultimately leads to bifurcation of the CNH domain, a presumptive stem cell pool in the tailbud, and formation of a secondary tail in BMP mutants. In parallel, the morphogenesis of tailbud cells is known to be under the control of noncanonical Wnt signaling, although the exact nature of the defect remains unclear. We find that inhibition of noncanonical Wnt signaling also leads to secondary tail formation. Additionally, we show that noncanonical Wnt signaling interacts with BMP signaling to maintain CNH integrity by affecting cadherin localization in CNH cells, possibly disrupting cell cohesion. We propose a model that BMP and a noncanonical Wnt pathway regulate tail morphogenesis by controlling cell migration and cell adhesion within the tailbud.
Keywords: Bone morphogenetic protein; WNT; Tailbud; Zebrafish; Biology, Genetics (0369)